Co-creating Agroecological Symbioses (AES) for Sustainable Food System Networks - Helenius, Juha; Hagolani-Albov, Sophia E.; Koppelmäki, Kari (Frontiers in Sustainable Food Systems, 2020)
Critics of modern food systems argue for the need to shift from a consolidated and concentrated, often monoculture based agro-industrial model toward diversified, post-fossil, and nutrient recycling food systems. The abundance of acute and obvious environmental problems in the agricultural sub-systems of the broader food system(s) have resulted in a focus on technological and natural scientific research into “solving” these point of production problems. Yet, there are many facets of food systems that are vital to sustainability which are not addressed even if the environmental problems were solved. In this article, we argue for agroecological symbiosis (AES) as a generic arrangement for re-configuring the primary production of food in agriculture, the processing of food, and development of a food community to work toward system-level sustainability. The guiding principle of this concept was the desire to base farming and food processing on renewable bioenergy, to close nutrient cycles, to break away from the consolidated food chain, to be more transparent and connected with consumers, and to revitalize the rural spaces where farms generally operate. Through a consistent and robust collaboration and co-creative process with transdisciplinary actors, ranging from food producers, and processers to policy actors, we designed a food system model based on networks of AES (NAES). The NAES would form place-based food networks, replacing the consolidated commodity chains. The NAES supports sustainable interactions from a biophysical and socio-cultural perspective. In this paper, we explain the AES concept, give an overview of the process of co-creating the pilot AES, and a proposal for the extension of the AES, as NAES, to create sustainable food systems. Overall, we conclude that the AES model holds potential for creating place-based food systems that further the sustainability agenda.